Software Tool for Optimal Placement and Sizing of Shunt Var Compensators in Power Systems (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper presents a MATLAB-based power system software tool, named as OPSVC for optimal placement and sizing of shunt Var compensators in both distribution and transmission systems. The OPSVC software incorporates the developed optimization algorithms and the backward/forward sweep ‎power flow and radial harmonic power flow methods in an open source environment. The capabilities of the OPSVC are that it can conduct several analyses, such as load flow, optimal placement and sizing of shunt capacitors, Static Var Compensator (SVC) and Static Synchronous Compensator (STATCOM) using different optimization techniques and plotting voltage profile of the studied system before and after installing reactive power compensators.